Performance Enhancement of Photovoltaic Panel Using Double-sides Water Glazing Chambers Cooling Technique - Mohammed, Farag Mahel; Mohammed, Jamal Abdul-Kareem; Sanad, Mustafa Abdul-Sayed (Al-Nahrain Journal for Engineering Sciences, 2019)
The efficiency of the solar PV panel decreases significantly as the PV panel’s operating temperature increases. There are many cooling techniques might be suitably deal with this problem to enhance the solar panel efficiency. The presented cooling technique used for solving the PV panel’s temperature elevation is an active close loop cooling system, accomplished using two water glazing chambers made from acrylic glass placed at the PV panel surfaces (rear and front). These champers are utilized for cooling down the PV cell’s temperature, as well as filtering the useful sunlight spectrum. The results show that the PV cell’s temperature reduction by 50.06% with using the cooling system, this leads to an average increase in the maximum output power and consequently electrical efficiency of the PV panel by about 12.69% and 14.2%, respectively.